2009
DOI: 10.1136/oem.2009.047431
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic strategies using physical examination are minimally useful in defining carpal tunnel syndrome in population-based research studies: Table 1

Abstract: Objective We evaluated the utility of physical examination maneuvers in the prediction of carpal tunnel syndrome (CTS) in a population-based research study. Methods We studied a cohort of 1108 newly employed workers in several industries. Each worker completed a symptom questionnaire, a structured physical examination, and nerve conduction study. For each hand, our CTS case definition required both median nerve conduction abnormality and symptoms classified as “classic” or “probable” on a hand diagram. We ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A minority of studies suggest that the prevalence of CTS may be as high as 3 % or 4 % [3]; however, most publications report a prevalence of approximately 2 % of the adult population in the USA, affecting 4-10 million patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A minority of studies suggest that the prevalence of CTS may be as high as 3 % or 4 % [3]; however, most publications report a prevalence of approximately 2 % of the adult population in the USA, affecting 4-10 million patients [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…We also chose this definition on the basis of evidence that these tests both demonstrate strong correlation with electrophysiologic diagnosis 21,31 . Typically, screening for cubital tunnel syndrome relies on multiple methods (patient-reported history of symptoms, clinical examination, electrodiagnostic testing, ultrasonographic examination) that all have diagnostic limitations 1,32,33 . Descatha et al demonstrated that the prevalence of carpal tunnel syndrome varied according to the case definition employed, leading to the misclassification of 1% to 10% cases.…”
mentioning
confidence: 99%
“…Although a neurological examination is central to the workup of patients with suspected neuropathies, it may not have adequate diagnostic accuracy. [4][5][6] Therefore, objective confirmation of a neuropathy and grading of severity may benefit patient management. 7 Nerve conduction studies (NCSs) provide the most objective and reliable diagnostic assessment of neuropathies.…”
mentioning
confidence: 99%